The Tyrosinase produced by Lentinula boryana (Berk. & Mont.) pegler suffers substrate inhibition by L-DOPA - Faria, Rodrigo Otavio de (Array, 2007)
We undertook a preliminary characterization of the tyrosinase produced by a strain of Lentinula boryana from Brazil, with a view to evaluate its potential for biotechnological applications. The enzyme was similar to other fungal tyrosinases in many respects. When the crude extract was characterized, the tyrosinase activity was optimal at pH=6 and was not particularly thermostable, with half-lives of about 10 min and 1 min at 50 and 60 °C, respectively. We purified the enzyme with ammonium sulfate precipitation followed by ion exchange chromatography on a DEAE Sepharose column, obtaining a yield of 33 % and a 5.3-fold enrichment. The purified preparation gave three bands on SDS-PAGE, with molecular masses of 20, 27 and 47 kDa. This preparation showed substrate inhibition kinetics with L-DOPA (3,4-dihydroxy-L-phenylalanine), with a KM of 1.9 mM and a KI of 72 mM. Under the same reaction conditions, a commercial mushroom tyrosinase followed Michaelis-Menten kinetics, with a KM of 0.51 mM. Although the present study did not identify properties that would make the tyrosinase of L. boryana more suitable in biotechnological applications than tyrosinases from other mushrooms, it has made a contribution by showing that the enzyme suffers substrate inhibition by L-DOPA, something that has not previously been reported for mushroom tyrosinases